Effects of Electron Beam Irradiation on Germination and Vigour of Greengram (Vigna radiata) Seeds - SHASHI BHALLA,; K. SRINIVASAN,; SUBADAS SINGH,; NEERAJ KUMAR,; R. PRAMOD,; S.C. BAPNA,; J. DWIVEDI,; ARUN SHARMA,; R.K. KHETARPAL, (Seed Research, 2026)
The full genetic potential of a crop can be realised by pre-treatment of seeds with plant growth regulators and chemicals enhancing the seed germination and seedling vigour. Therefore, the present study was conducted to evaluate the effects of electron beam (EB) irradiation on greengram (Vigna radiata) seeds. For this purpose, dry seeds of greengram were exposed in a single layer to EB doses, viz. 170, 340, 510, 680, 850, 1020, 1190 and 1360 Gy at an energy level of 500 keV produced from a 750 keV, 20 kW DC accelerator. Irradiated seeds along with the control (unirradiated) were subjected to standard seed germination test and shoot length, root length, seedling vigour and vigour index. The seeds were also subjected to electrical conductivity and tetrazolium test for viability. Results showed that irradiation with EB doses as above have no significant effects on seed germination but affected seedling vigour and vigour index. The lower doses, viz. 170, 340 and 510 Gy had stimulatory effect on seedling vigour which were 37.69, 35.69, and 33.70 as compared to 30.19 in the control. Corresponding to this the seedling vigour index showed a decline @ 680 Gy. The electrical conductivity of seed leachate of the control and irradiated samples exhibited nearly a similar trend.